Gas-water interaction in confined space of shale kerogen - Chu ZHANG; Yanbin YAO; Peng FENG; Yuheng ZHANG (Meitan xuebao)
Understanding the shale matrix-fluid interactions is crucial for evaluating gas-in-place resources and the gas production potential in shale gas reservoirs. However, due to the assumptions of mathematical characteristic models, the existing research on the characterization of gas-water adsorption behavior and its occurrence patterns in nanopores with different scales is still incomplete, resulting in the mechanism of gas-water interaction in confined spaces still unclear. Methane adsorption experiments on six Longmaxi Formation shale kerogen were carried out under dry and wet conditions. Then, molecular simulation and an improved Ono–Kondo model were used to analyze the methane adsorption behaviors. Finally, the mechanism of gas-water interaction in micro nano confined spaces was discussed. Results show that under dry condition, methane adsorbed in the form of pore-filling contributes dominantly to the total methane adsorption amount. Pore-filling adsorption mainly occurs in micropores, while surface adsorption mainly occurs in mesopores. Under wet condition, the adsorption behavior of methane changes significantly. Samples that were originally adsorbed mainly by pore-filling under dry condition were transformed to be absorbed mainly by surface adsorption. The clustered distribution of water molecules drives methane to high-energy sulfur-containing sites by occupying the micropore space, resulting in a significant reduction in the filling adsorption capacity of methane. In contrast, due to the difference in adsorption sites between water molecules and methane, the influence of water molecules on the surface adsorption behavior of methane in mesopores is relatively small.